Genome-scale measurement of off-target activity using Cas9 toxicity in high-throughput screens - David W. Morgens (Nature Portfolio, 2017)
CRISPR-Cas9 screens are powerful high-throughput tools but can be confounded by nuclease toxicity. Here the authors design a library of variable length gRNAs with thousands of negative controls, including the targeting of ‘safe’ loci to account for on-target site DNA damage toxicity.